PENERAPAN MODEL PEMBELAJARAN BASED LEARNING (PBL) MELALUI MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KEMAMPUAN MENULIS BAHASA INGGRIS - Herlyna Manaf (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This research aims to apply the Problem Based Learning (PBL) learning model through series of image media to improve English writing skills at SMA Negeri 4 Pekanbaru. This type of research uses Classroom Action Research (PTK). The research subjects were class X students at SMA Negeri 4 Pekanbaru. In implementing the action, it is carried out in 2 cycles, namely cycle I and cycle II. The activities carried out in each cycle consist of planning, implementation, observation and reflection. The results of the research show an increase in English writing skills through serial image media. significant increase in students' understanding of concepts, writing skills, and learning motivation. The integration of serial image media as a supporter of PBL provides a visual dimension that helps students understand the content, stimulates creativity, and increases active involvement in the learning interaction process.